Comparison between three different high fluence UVA levels in corneal collagen cross-linking for treatment of experimentally induced fungal keratitis in rabbits. Issue 4 (July 2022) - Awad, Ramy; Hafezi, Farhad; Ghaith, Alaa Atef; Baddour, Manal Mohammad; Awad, Khaled; Abdalla, Moones; Sheta, Eman; Sultan, Gehad Mahmoud; Elmassry, Ahmed
Introduction: The aim of this study was to compare the efficacy of Photo-Activated Chromophore for Keratitis – Corneal Collagen Cross-linking (PACK-CXL) of three different total UVA fluence levels and topical voriconazole in treatment of fungal keratitis experimentally induced in rabbits. Methods: This is an interventional experimental study including both eyes of 16 rabbits (32 eyes). Fungal keratitis was induced by intrastromal injection of Fusarium Solani into the cornea. The rabbits were then divided into four groups (8 eyes for each) from which group A received Voriconazole eye drops and considered as control group. Group B, C, D received single PACK-CXL session with total fluence levels of 7.2, 10.0 and 15.0 J/cm2 for each respectively. Daily clinical examination was recorded and all corneas were removed for microbiology and histopathology on day ten. Results: The mean clinical signs score eyes treated with high fluence PACK-CXL showed evident clinical improvement from fourth to tenth day of treatment. This improvement was equivalent to that of Voriconazole treatment. The results showed better improvement with increasing the UVA total fluence levels but this difference was not statistically significant (P < 0.05). Similarly, the median CFU/ml declined on increasing UVA fluence but with no statistically significant values. Histopathological examination revealed better improvement of inflammatory signs on higher fluence levels compared to lower ones. Conclusions: High intensity PACK-CXL (30 mW/cm 2 ) was as effective as Voriconazole in the treatment of fungal keratitis in rabbits. Increasing the fluence of UVA was associated with slightly better clinical outcomes with no added risks. More clinical studies are needed to confirm these results.